Corporate taxation and productivity catch-up: evidence from European firms - Gemmell, Norman; Kneller, Richard; McGowan, Danny; Sanz, Ismael; Sanz-Sanz, José F. (Wiley, 2016)
This paper explores whether higher corporate tax rates reduce the speed with which small firms converge to the productivity frontier by lowering the after-tax returns to productivity-enhancing investments. Using data for 11 European countries we find evidence that their productivity catch-up is slower the higher are statutory corporate tax rates. In contrast, we find large firms are instead affected by effective marginal rates. Using the reduced form model of productivity convergence due to Griffith et al. (2009) our results are robust to a host of robustness checks and a natural experiment that exploits the 2001 German tax reforms.